Особливості земельних відносин у Кримському ханстві (1449–1783 рр.) - Бурдін, М. Ю.; Burdin, M. Yu.; ResearcherID: B-8227-2018; Mykhailo Burdin (Вісник Харківського національного університету внутрішніх справ. - 2017. - № 4 (79). - С. 26-34, 2017)
Розглянуто основні форми землеволодіння, які існували у Кримському ханстві. З’ясовано особливості ханського землеволодіння, сутність таких форм земельної власності, як кагалик, бейлік, мевкуфе. Особливу увагу приділено характеристиці селянського общинного землеволодіння – джемаату. Доведено, що особливості земельних відносин у татарському середовищі виникли значною мірою під впливом релігійних норм шаріату.

The basic forms of land possession in the Crimean Khanate during the XV– XVIII centuries have been considered and their specific features have been determined. It has been noted that the Khan lands were the largest form of state land possession. A special form of land possession was “kalhalyk” – it is a parcel of land that was owned by the heirs of the khans. The form of land possession, where the state law inferior to the private, patrimonial one, were medieval Turkish principalities – the possession of each of the six leading tataric generations. Another form of land possession, which combined elements of both state and private property rights, was hodzhalyk – a special area under the control of Khidrs – spiritual mentors. Murzinske was one of the most common forms of private land possession in the Crimean Khanate. It arose as a result of a pledge for the service of lands that were previously part of the Khan’s domain. Peasant land possession consisted, first of all, of isolated land plots within the Khan, Bei, Murzin land holdings, which were considered to be the property of certain peasants, and secondly, land allotments considered as property of the entire community. It was the lands of the second group that consisted of the so-called jemaat. Analysis of the content of the Khan’s labels and court decisions of the XVI–VIII centuries indicates that jemaat was a full-fledged socio-economic unit in the Khanate. A special form of land possession in the Crimean Khanate was the endowment – the land plots belonging to the clergy. This type of land possession arose under the influence of religious norms of Islam regarding the dedication of the land to Allah, it could not be alienated. The endowment could not be also presented, sold or confiscated. It has been argued that land relations on the territory of the peninsula were characterized by a gradual complication, which was accompanied by an increase in the value of land holdings, the transfer of a part of the land fund to private ownership and a significant influence of the religious norms of moslem sacred law on the state of land relations in the Crimean Khanate.

Рассмотрены основные формы землевладения, которые существовали в Крымском ханстве. Выяснены особенности ханского землевладения, сущность таких форм земельной собственности, как кагалик, бейлик, мевкуфе. Особое внимание уделено характеристике крестьянского общинного землевладения – джемаата. Доказано, что особенности земельных отношений в татарской среде возникли в значительной степени под влиянием религиозных норм шариата.
Features of land relations in the Crimean Khanate (1449–1783)
Особенности земельных отношений в Крымском ханстве (1449–1783 гг.)
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; Кримське ханство; землеволодіння; шаріат; бейлік; джемаат; вакуф; земельні відносини; Crimean Khanate; land possession; moslem sacred law; medieval Turkish principality; jemaat; endowment; Турція; середньовічна історія; Крымское ханство; землевладение; шариат; бейлик; Turkey